2020
DOI: 10.1111/padr.12358
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Proximity to Death, and Religiosity

Abstract: Considerable evidence has documented that the elderly are more religious and that religiosity is associated with better health and lower mortality. Yet, little is known about the reverse role of life expectancy or proximity to death, as opposed to age, for religiosity. This paper provides evidence for the distinct role of expected remaining life years for the importance of religion in individuals' lives. We combine individual survey response data for more than 300,000 individuals from 95 countries over the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Meeting the spiritual needs of older adults was an important factor in achieving active aging and their beliefs were essential in adapting to the challenges of aging (50); aging increases people's religious beliefs and desire to participate in spiritual rituals (51). According to the literature, the presence and involvement of older people in religious ceremonies and activities can reduce their stress from aging consequences (50), improve their life satisfaction (52), enhance their motivation to create and strengthen self-care behaviors, and subsequently improve their level of health and active aging (53).…”
Section: Discussionmentioning
confidence: 99%
“…Meeting the spiritual needs of older adults was an important factor in achieving active aging and their beliefs were essential in adapting to the challenges of aging (50); aging increases people's religious beliefs and desire to participate in spiritual rituals (51). According to the literature, the presence and involvement of older people in religious ceremonies and activities can reduce their stress from aging consequences (50), improve their life satisfaction (52), enhance their motivation to create and strengthen self-care behaviors, and subsequently improve their level of health and active aging (53).…”
Section: Discussionmentioning
confidence: 99%
“…The psychological, physical, and relational consequences of the loss of an adult child are substantial. In facing such adversity, it would make sense intuitively that older adults would turn to religion for strength since older adults tend to be more religious, in general, than younger individuals (Lechler & Sunde, 2020). Interestingly, however, this scoping review of the literature indicates that while religiosity may not necessarily be enhanced, religious beliefs provide a framework for understanding the loss and may underpin grief responses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown an increase in religiosity with age, and older people tend to be more religious than younger generations (21,22). Volunteering, grandparenting, community participation and religious participation were used as indicators for assessing social participation in the present study.…”
Section: Social Participationmentioning
confidence: 99%